Plant cytokinesis requires de novo secretory trafficking but not endocytosis - Reichardt, Ilka; Schumacher, Karin (Current biology, 2007)
Summary During plant cytokinesis membrane vesicles are efficiently delivered to the cell-division plane, where they fuse with one another to form a laterally expanding cell plate [1, 2]. These membrane vesicles were generally believed to originate from Golgi stacks. Recently, however, it was proposed that endocytosis contributes substantially to cell-plate formation [3]. To determine the relative contributions of secretory and endocytic traffic to cytokinesis, we specifically inhibited either or both trafficking pathways in Arabidopsis. Blocking traffic to the division plane after the two pathways had converged at the trans-Golgi network disrupted cytokinesis and resulted in binucleate cells, whereas impairment of endocytosis alone did not interfere with cytokinesis. By contrast, inhibiting ER-Golgi traffic by eliminating the relevant BFA-resistant ARF-GEF [4] caused retention of newly synthesized proteins, such as the cytokinesis-specific syntaxin KNOLLE in the ER [5], and prevented the formation of the partitioning membrane. Our results suggest that during plant cytokinesis, unlike animal cytokinesis, protein secretion is absolutely essential, whereas endocytosis is not.